Występowanie kornika drukarza Ips typographus (L.) i rytownika pospolitego Pityogenes chalcographus (L.) w drzewostanach świerkowych uszkodzonych przez wiatr w Górach Świętokrzyskich - Borkowski, Andrzej (Leśne Prace Badawcze, 2011)
The aim of this study was to assess the density and sex ratio of the Ips typographus population and associated species in managed spruce stands growing in the territory of the Zagnańsk Forest District. In June and July of 2008 and 2009, colonisation of 30 windfalls was assessed using entomological section-based analysis. During the research period, I. typographus infested all investigated trees colonising their entire lengths from top to bottom except for the stem section covering height increments from the previous and current years (100% frequency in stem sections). Stem infestation density indicators in the years 2008-2009 were 466 and 455 maternal galleries m -2 , respectively. The sex ratio of the I. typographus population points to an increase in this pest species, since there were twice as many females as males in the population (67 – 67.5%). The uniform distribution of egg galleries on the stems and the lack of a relationship between the diameter of stem sections and their infestation density ( r = -0.0447, P = 0.3126) indicate that I. typographus can infest a wide range of thicknesses of breeding material giving it a broad habitat tolerance. Pityogenes chalcographus (L.) primarily accompanied I. typographus , and it exhibited a similar average infestation density in both seasons, ranging from 68 to 71 egg galleries m -2 on those spruce trees that were examined. A positive correlation between the density of I. typographus maternal galleries and the density of P. chalcographus egg galleries ( r = 0.3766, P = 0.0001) indicates an overlap between the ecological niches of these bark beetle species. These results may suggest that under favourable weather conditions there is a genuine risk of bark beetle outbreaks in the territory of the Zagnańsk Forest District.